Focusing device based on overconstrained mechanism. (August 2019) - Racila, L D; Dumitru, I; Tutunea, D; Matei, L; Geonea, I; Otat, O; Racila, M
Abstract: The paper presents an application based on a very special 6R overconstrained mechanism. This mechanism is started from 6R Wohlhart symmetric mechanism, not in its classical spatial position but in a different one, with three non-adjacent joints constrained to remain in a fixed plane. This disposition allows the conception of an interesting device, a focusing table, capable to obtain a good accuracy.